Napięcie kosztem pretekstu. O adaptacji filmowej „Przygody Stasia" Bolesława Prusa - Pławuszewski, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
Przygoda Stasia (Stas’ Adventure) – a short story by Boleslaw Prus (first printed in the magazine „Kłosy” in 1879) – became the subject of a film adaptation released in 1970 under the same title, directed by Andrzej Konic. This television movie deserves research attention for at least two reasons. Firstly, it is a work that, in the context of the history of Polish cinema, has been doomed to almost complete oblivion. It is worth asking about the reasons for this and attempting to reconstruct the historical and filmmaking circumstances of the film’s creation. Secondly, adaptation processes should be analyzed and interpreted (here: in relation primarily to the plot issues and the construction of the presented world).